Nonlinear Impact of Public Debt on Economic Growth: Evidence from Sub-Saharan African Countries - (:unkn) unknown (My University, 2019)
This paper empirically explores the impact of public debt on economic growth in Sub-Saharan African (SSA) countries over the period 1960 to 2015 by using a system Generalized Methods of Moments (s-GMM). Specifically, this work studies the nonlinear relationship between public debt and economic growth. To do so, we perform the Sasabuchi-Lind-Mehlum's test (or U-test) to check if the required and sufficient conditions are met for an inverted U-shape. The results strongly suggest the presence of a nonlinear relationship between public debt and economic growth. By applying the Delta method, this threshold is evaluated at about 36.18 percent ratio debt-to-GDP with its confidence interval associated (13, 59). The public debt boosts the economic growth when its level is less than this turning point. Above this threshold, an increase in public debt would lower the economic growth. Accordingly, a re-examination of the public debt level of some convergence policies which set this level (debt-to-GDP ratio) to 70 per cent (cf. and 2) is proposed.
Keywords: African Research